An MRI-Compatible System for Characterizing Supraspinal Processing of Walking-Related Foot-Sole Somatosensory Stimulation - Hao Yue; Bin Shen; Yishu Chen; Yufeng Zhang; Jiaojiao Lu; Shaobo Li; Brad Manor; Weijie Fu; Junhong Zhou (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Foot soles are the only part in direct contact with the ground during walking. The mechanoreceptors on foot soles continuously obtain somatosensory information (e.g., ground reaction forces) that is delivered to spinal and supraspinal networks. The timely and accurate supraspinal processing of such information, which can be captured by the activation of the supraspinal regions, is critical to the regulation of walking. However, little is known about supraspinal somatosensory processing related to walking. Characterizing the supraspinal response to walking-related somatosensory inputs using MRI is challenging, because individuals are required to stay motionless during MRI scan. We thus developed a stimulation system that simulates the amplitude and timing of foot-sole pressure changes experienced during each step of overground walking, without inducing significant head motion. In the study to examine its validity and reliability of simulation, seven younger adults completed two trials of eight-meter walking. The temporal changes of foot-sole pressure of each step during walking were recorded using a pressure insole and used to program the motion of the system. The results indicated high validity and reliability of the stimulation (rho $= 0.94\sim 0.98$ , p<0.0001). Phantom imaging test revealed that the signal-to-noise ratio of the MR image when the system working was similar to when the system was off, suggesting excellent MRI compatibility. Finally, block-designed test indicated that, compared to rest, multiple supraspinal regions (e.g., postcentral gyrus) were activated (p<0.005) by foot-sole stimulation. This MRI-compatible system provides a novel approach to characterizing the supraspinal sensorimotor control of walking via MRI.